Pyruvate uptake is inhibited by valproic acid and metabolites in mitochondrial membranes - Aires, Catia C. P. (2015)
The pyruvate uptake rate in inverted submitochondrial vesicles prepared from rat liver was optimized and further characterized; the potential inhibitory effects of the anticonvulsive drug valproic acid or 2-n-propyl-pentanoic acid (VPA), Delta(4)-valproic acid or 2-n-propyl-4-pentenoic acid and the respective coenzyme A ( CoA) conjugates were studied in the presence of a proton gradient. All tested VPA metabolites inhibited the pyruvate uptake, but the CoA esters were stronger inhibitors (40% and 60% inhibition, respectively, for valproyl-CoA and Delta(4)-valproyl-CoA, at 1 mM). At the same concentration, the specific inhibitor 2-cyano-4-hydroxycinnamate decreased the pyruvate uptake rate by 70%. The reported inhibition of the mitochondrial pyruvate uptake may explain the significant impairment of the pyruvate-driven oxidative phosphorylation induced by VPA. (C) 2008 Federation of European Biochemical Societies. Published by Elsevier B. V. All rights reserved.. - Fundacao para a Ciencia e a Tecnologia (FCT) , Lisboa, Portugal [POCTI/FCB/48800/2002]; FEDER ; [SFRH/BD/22420/2005]. - This work was financially supported by Fundacao para a Ciencia e a Tecnologia (FCT), Lisboa, Portugal (POCTI/FCB/48800/2002 with partial funding of FEDER and SFRH/BD/22420/2005).